2019
DOI: 10.1097/cmr.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations associated with acquired resistance to BRAFV600E targeted therapy in melanoma cells

Abstract: Selective inhibition of the mutant BRAF protein is a highly promising therapeutic approach for melanoma patients carrying the BRAF V600E mutation. Despite the remarkable clinical response, most patients develop resistance and experience tumour regrowth. To clarify the molecular background of BRAF inhibitor resistance, we generated four drug-resistant melanoma cell lines from paired primary/metastatic cell lines using a vemura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Overexpressed genes in BRAF inhibitor-resistant cells are often associated with growth factors and their receptors, cell adhesion molecules and extracellular matrix binding [ 84 ]. Common mutations involve effects on receptor tyrosine kinases (RTKs), such as epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGFR), hepatocyte growth factor (HGF), or insulin-like growth factor (IGF) receptor, which in turn activate parallel pathways [ 11 , 19 , 20 , 25 , 29 , 58 , 59 , 84 , 85 , 86 ]. Research has shown extensive redundancy in RTK-mediated signaling pathways, whereby a broad range of widely expressed RTKs are upregulated in cells with BRAF inhibitor resistance [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overexpressed genes in BRAF inhibitor-resistant cells are often associated with growth factors and their receptors, cell adhesion molecules and extracellular matrix binding [ 84 ]. Common mutations involve effects on receptor tyrosine kinases (RTKs), such as epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGFR), hepatocyte growth factor (HGF), or insulin-like growth factor (IGF) receptor, which in turn activate parallel pathways [ 11 , 19 , 20 , 25 , 29 , 58 , 59 , 84 , 85 , 86 ]. Research has shown extensive redundancy in RTK-mediated signaling pathways, whereby a broad range of widely expressed RTKs are upregulated in cells with BRAF inhibitor resistance [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Development of acquired resistance after initial response leads to tumour regrowth [24]. Both genetic and epigenetic alterations are involved in the development of acquired resistance [2].…”
Section: Discussionmentioning
confidence: 99%
“…Resistant cell lines were established as described before, by continuously increasing the concentration of Vemurafenib analogue PLX4720 with every passage for 3 months [24]. In brief, WM983A, WM983B cell lines were seeded at low densities in T25 flasks until cell confluence reached about 80%.…”
Section: Establishment Of Braf Inhibitor Resistant Cell Linesmentioning
confidence: 99%
“…This triggers then constant proliferation in melanoma cells, leading to melanoma and treatable well by by a combination of B-Raf and MEK inhibitors (e.g., vemurafenib and cobimetanib). However, resistance is an issue of the treatment with these inhibitors and additional therapeutic options are necessary such as ERK1/2 inhibitors or alternative targeting strategies of protein kinases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it describes and models all nodes of the whole network considered and this for all time points and all desired pharmacological interventions. Nevertheless, for each real situation, comparison and validation by experimental data is critical and also here the ERK cascade is a nice and well-studied example (e.g., [7,8,9,10,11,14]).…”
Section: Introductionmentioning
confidence: 99%